1988
DOI: 10.1136/vr.122.14.325
|View full text |Cite
|
Sign up to set email alerts
|

Cortical function in cattle during slaughter: conventional captive bolt stunning followed by exsanguination compared with shechita slaughter

Abstract: Brain function was examined in adult cattle after conventional captive bolt stunning or shechita slaughter, using eight animals in each treatment. The times to loss of evoked responses (visual and somatosensory) and spontaneous activity in the electro-corticogram were used to determine the onset of brain failure. Captive bolt stunning followed by sticking one minute later resulted in immediate and irreversible loss of evoked responses after the stun. Spontaneous cortical activity was lost before sticking in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 0 publications
1
53
0
2
Order By: Relevance
“…During our experiment, calves in an inverted or upright position lost consciousness, based on EEG recordings, 49 ± 25 and 109 ± 32 s, respectively (mean ± SD), after the neck cut. Previous studies in cattle indicated loss of consciousness ranging from 10 s up to over 3 min after the neck cut (Daly et al, 1988;Gregory et al, 2010;Bourguet et al 2011). Newhook andBlackmore (1982) suggested the possibility of an intermittent return to consciousness for up to 123 to 323 s after non-stunned slaughter in cattle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During our experiment, calves in an inverted or upright position lost consciousness, based on EEG recordings, 49 ± 25 and 109 ± 32 s, respectively (mean ± SD), after the neck cut. Previous studies in cattle indicated loss of consciousness ranging from 10 s up to over 3 min after the neck cut (Daly et al, 1988;Gregory et al, 2010;Bourguet et al 2011). Newhook andBlackmore (1982) suggested the possibility of an intermittent return to consciousness for up to 123 to 323 s after non-stunned slaughter in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable variation between cattle in time to loss of consciousness after the neck cut. Some studies suggest a rapid loss of consciousness (4 to 7 s) in cattle after the neck cut (Nangeroni and Kennett, 1963;Bager et al, 1992) whereas other studies report a spontaneous loss of brain activity 75 ± 48 s after the neck cut (range 19 to 113 s) and the possibility of an intermittent return to consciousness for up to 123 to 323 s after slaughter (Newhook and Blackmore, 1982;Daly et al, 1988). There is substantial debate about which indicators most adequately assess unconsciousness at slaughter and which merit further investigation (European Food and Safety Authority (EFSA), 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The bolt penetrating the skull usually causes immediate unconsciousness, as demonstrated in experimental animals by a loss of visually evoked potentials (7) as weIl as a loss of corneal reflexes, depending on the localization of the injury (8,9). It has also been shown in experimental animals, however, that captive bolt injury of the brain is not necessarily associated with unconsciousness (9,10) and that cerebral function can-at least partly-be restored, as indicated by the reappearance of acoustically or visually evoked potentials (11).…”
Section: Discussionmentioning
confidence: 99%
“…In this region immediately caudal to the skull will be portions of the rete mirabile-a specific adaptation of the vascular system of marine mammals which appears to function to buffer pressure (and perhaps pH and oxygenation levels) in blood circulation to the brain (Lin, Lin, & Chou, 1998;Melnikov, 1986;Nagel, Morgane, McFarlan, & Galliano, 1968 Ellendorf, 1988). In the case of the use of the rod, after the operative has used the rod to cause tissue damage, a wooden peg is inserted into the hole created by the rod (see Figure 1).…”
Section: Resultsmentioning
confidence: 99%